The difference between standing and sitting in 3 different seat inclinations on abdominal muscle activity and chest and abdominal expansion in woodwind and brass musicians - Ackermann, Bronwen J.; O'Dwyer, Nicholas; Halaki, Mark (Frontiers in Psychology, 2014)
Wind instrumentalists require a sophisticated functioning of their respiratory system to control their air stream, which provides the power for optimal musical performance. The air supply must be delivered into the instrument in a steady and controlled manner and with enough power by the action of the expiratory musculature to produce the desired level of sound at the correct pitch. It is suggested that playing posture may have an impact on the abdominal muscle activity controlling this expired air, but there is no research on musicians to support this theory. This study evaluated chest and abdominal expansion, via respiratory inductive plethysmography, as well as activation patterns of lower and upper abdominal musculature, using surface electromyography, during performance of a range of typical orchestral repertoire by 113 woodwind and brass players. Each of the five orchestral excerpts was played in one of four randomly allocated postures: standing; sitting flat; sitting inclined forwards; and sitting inclined backwards. Musicians showed a clear preference for playing in standing rather than sitting. In standing, the chest expansion range and maximum values were greater (p<0.01), while the abdominal expansion was less than in all sitting postures (p<0.01). Chest expansion patterns did not vary between the three sitting postures, while abdominal expansion was reduced in the forward inclined posture compared to the other sitting postures (p<0.05). There was no significant variation in abdominal muscle activation between the sitting postures, but the level of activation in sitting was only 2/3 of the significantly higher level observed in standing (p<0.01). This study has demonstrated significant differences in respiratory mechanics between sitting and standing postures in wind musicians during playing of typical orchestral repertoire. Further research is needed to clarify the complex respiratory mechanisms supporting musical performance.